Innovative Techniques for Assessment of Land Capability Using Soil Conditions and GIS - Mona Hefni Mohamed Kenawy and Abdellatif Deyab Abdellatif, Mohamed El Sayed Abou Kota*, Shimaa Kamal Ganzour (Journal of the Indian Society of Soil Science, 2022)
Recently, an urgent matter in the 2030 strategy is the land capability classification (LCC), in line with the specific potential of the area. From that, this study was implemented based on spatial databases in a geographic information system (GIS) environment. The results on LCC exhibited that Class II good criteria are focused in the following profiles 1 to 5 where indicators were between 61.3 to 74.5% covering an area of 20709.5 ha and Class III fair criteria in profiles 6 to 15, where indicators were between 39.8 to 57.6% with an area of 36531.8 ha. The potential re-evaluation of land capability by addressing soil salinity indicated that profile 2 showed excellent criteria for Class I, where the indicator was 80.8% with an area of 306.5 ha, Class II Good criteria are concentrated in the following profiles 1, 3, 4, 5, 7, 8, 12, 13 and 15 where indicators were between 60.0 to 78.9% with an area 49035.8 ha. Class III Fair criteria are resolute in the following profiles 6, 9, 10, 11 and 14 where indicators were between 46.9 to 57.8% with an area of 7899 ha. The study showed the effectiveness of the role of remote sensing techniques and GIS in the sustainable development and management of soil resources.